The Welfare Analysis of Product Innovations, with an Application to Computed Tomography Scanners - Trajtenberg, Manuel (Journal of Political Economy, 1989)
The main goal of this paper is to put forward a methodology for the measurement of product innovations using a value metric, that is, equating the "magnitude" of innovations with the welfare gains they generate. This research design is applied to the case of computed tomography scanners, a revolutionary innovation in medical technology. The econometric procedure centers on the estimation of a discrete choice model (the nested multinominal logit), which yields the parameters of a utility function defined over the changing quality dimensions of the innovative product. The estimated flow of social gains from innovation is used to compute a social rate of return to R & D, to explore the interrelation between innovation and diffusion, and to trace the time profile of benefits and costs, the latter suggesting the possible occurrence of "technological cycles."